Targeting Adhesion Molecules in Cardiovascular Disorders - Haverslag, Rene; Pasterkamp, Gerard; Hoefer, Imo E. (Cardiovascular & Haematological Disorders - Drug Targets, 2008)
Cell adhesion molecules are ubiquitously expressed proteins playing a central role in controlling cell migration, proliferation, survival, and apoptosis. Besides their key function in physiological maintenance of tissue integrity, adhesion molecules play an eminent role in various pathological processes. In cardiovascular disorders, cell adhesion molecules are particularly involved in atherogenesis and atherosclerotic plaque progression. They also play a critical role in myocardial infarction and reperfusion damage and a minor role in valvular stenosis and cardiomyopathy. Their common denominator: An increased expression of adhesion molecules involved in leukocyte extravasation and accumulation. Leukocyte extravasation is a multistep process, mediated by several cell adhesion molecules including selectins (P-, E- and L-), integrins and members of the Ig superfamily (ICAM-1, VCAM-1). These molecules can be targeted for imaging purposes (e.g. to identify atherosclerotic plaques) or can serve as biomarkers for plaque destabilization. Furthermore, cell adhesion molecules can serve as drugable targets to prevent leukocyte extravasation where warranted to decrease inflammatory tissue damage (e.g. reperfusion injury). Current techniques involve blocking of binding sites, targeted drug delivery using liposomes and polymeric particles as carriers or imaging of inflammation sites using labeled cells or antibodies. This review focuses on the role of cell adhesion molecules in cardiovascular disease and the use of targeting adhesion molecules for imaging purposes and local drug delivery in cardiovascular medicine.
Keywords: cardiovascular disorders